Investigation of the forced-convection heat-transfer in the boiler flue-gas heat recovery units employing the real-time measured database. (1st January 2022) - Zhang, Wei; Wang, Suilin; Mu, Lianbo; Jamshidnia, Hamid; Zhao, Xudong
Abstract: Extra moistures condensation and extraction from the boiler flue-gas have been proven to be an effective measure to enhance the thermal efficiency of the boiler system. Previous researches on the condensing flue-gas heat recovery unit was based on the controlled lab condition or instant site measurement which was unable to reflect the long-term real performance of the boiler system with flue-gas heat recovery units. This research employed the real-time measurement database established between 2008 and 2019 to investigate the heat transfer at the flue-gas heat recovery unit. This solution can evaluate the long-term dynamic heat-transfer performance of the flue-gas heat recovery unit. A semi-experimental formula was established to address the relationship between the dew point temperature and heat transfer coefficient of the flue gas. It was found that the heat-transfer coefficient is sensitive to the inlet temperature of cooling water. Further, a dimensionless formula was established to address the relation among the convection heat-transfer coefficient and its other operational parameters. The all-applicable criterion equation that can judge the heat and mass transfer performance of flue-gas heat recovery units, and assess the energy saving potential of the boiler system with such a unit. Highlights: The long-term real-time measurement database were concluded and analyzed. The heat-transfer coefficient is sensitive to the inlet temperature of cooling water. Self-designed heat recovery units improved the thermal efficiency by 7.4 %–12.5 %. Established formula can be reference for primary design and economical evaluation.